1980
DOI: 10.1021/j100460a021
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of some chemisorbed molecules on tungsten oxide-silica

Abstract: Transparent plates of a tungsten oxide-silica metathesis catalyst were prepared by hydrolyzing a WCl6-Si(OC2H6)4 mixture. From the infrared spectra of adsorbed pyridine and ammonia, it is concluded that the chemisorption sites on the catalyst surface are of the Lewis type. Strong Bronsted acid sites could not be observed: the surface hydroxyls appear to resemble the weakly Bronsted-acidic hydroxyls on dry silica gel. Temperature-programmed reduction showed that ~95% of the tungsten on the calcined catalyst is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 2 publications
0
21
0
Order By: Relevance
“…8,[10][11][12][13][14][15] Among them, it was reported that the tungsten dispersion, tetrahedral tungsten oxide species, intermediate WO 3Àx , or W 5+ species are the active sites for metathesis, [16][17][18][19] and that WO 3 crystals are not active in metathesis and catalyst sites should be contained in the amorphous surface. 8,20 At present, the activation by pretreatment conditions to improve performance of supported WO x /SiO 2 catalysts in metathesis reaction has received much attention because of pre-activating the active sites of catalysts to form the activated state before running the reaction.…”
Section: 9mentioning
confidence: 99%
“…8,[10][11][12][13][14][15] Among them, it was reported that the tungsten dispersion, tetrahedral tungsten oxide species, intermediate WO 3Àx , or W 5+ species are the active sites for metathesis, [16][17][18][19] and that WO 3 crystals are not active in metathesis and catalyst sites should be contained in the amorphous surface. 8,20 At present, the activation by pretreatment conditions to improve performance of supported WO x /SiO 2 catalysts in metathesis reaction has received much attention because of pre-activating the active sites of catalysts to form the activated state before running the reaction.…”
Section: 9mentioning
confidence: 99%
“…The irst studies were made by Raman and led to the conclusion that the active site was an isolated surface complex of tungsten but of unknown structure [43]. The irst postulated surface species was a pentacoordinated tungsten complex but no experimental justiication was given [44].…”
Section: Solids Containing Group VI (Mo W) Metal Ions Used In Heteromentioning
confidence: 99%
“…The proton comes from the interaction of the reactant alkene with the non-reduced surface species. Adsorption of 1-hexene and hydrogen addition yield an intermediate which through back donation of the proton gives a carbenoid chain initiator [8]. The key intermediate in the metathesis reaction is believed to be a metallocyclobutane complex that forms around this carbene center.…”
Section: )mentioning
confidence: 99%
“…The methyl alkylidene is reused in another metathesis cycle. A limited number of metatheses proceed through the initiator before the chain of reactions terminates [8].…”
Section: )mentioning
confidence: 99%